THE RELATIONSHIP OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR, ORGANIZATIONAL COMMITMENT, AND JOB SATISFACTION WITH NURSES’ PERFORMANCE IN INPATIENT CARE SETTINGS - Sri Wahyuni Nasution; Saud Parulian Harianja; Chrismis Novalinda Ginting (International Archives of Medical Sciences and Public Health, 2025)
This study investigates the relationship of organizational citizenship behavior, organizational commitment, and job satisfaction, with the performance of inpatient nurses at RSU Royal Prima Medan (RPMH). Aquantitative correlational (explanatory) design was employed, involvinga total sample of 151 nurses in 2024. Data analysis was conducted using univariate, bivariate, and multivariate techniques. The findings reveal that organizational citizenship behavior, rganizational commitment, and job satisfaction are significantly associated with nurse performance, with job satisfaction demonstrating the strongest correlation. Theseresults underscore the importance of strengthening job satisfaction and organizational factors to enhance nurse performance and improve overall hospital service quality.